Countermovement jump performance is not affected during an in-season training microcycle in elite youth soccer players - Malone, J. J.; Murtagh, C. F.; Morgans, R.; Burgess, D. J.; Morton, J. P.; Drust, B. (The Journal of Strength and Conditioning Research, 2015)
This study examined the change in countermovement jump (CMJ) performance across a microcycle of training in professional soccer players during the in-season period. Nine elite youth soccer players performed a CMJ test before and after 4 consecutive soccer training sessions of an in-season weekly microcycle. Training load was quantified using global positioning systems, heart rate, and rating of perceived exertion. Absolute change (before to after training) in CMJ height across each training session was analyzed using one-way repeated-measures analysis of variance. Magnitude of effects was reported with the effect size (ES) statistic. Correlation analyses assessed the relationships between training load measures and the absolute change in CMJ height. Training load remained similar on all training days apart from a significant decrease in training load (all variables except high-speed distance) on the last training session (p = 0.05). No significant difference was found for CMJ height (p = 0.23) across the training microcycle (ES range, -0.04 to -0.22). No correlations were found between training load variables and absolute change in CMJ height (range: r = -0.21 to 0.22; p > 0.05). This study revealed no significant change in CMJ performance across the in-season microcycle. This finding suggests that soccer players are able to maintain CMJ performance across an in-season training microcycle.